Features of the development of research competence in future special education teachers - Yerzhanova, Gulnur; Autayeva, Akbota; Mazhinov, Bagdat; Iralina, Mira; Nishanbayeva, Sabira (Frontiers in Education, 2025)
IntroductionDeveloping research competence is essential for future special education teachers to effectively analyze educational practices, conduct pedagogical research, and innovate teaching strategies for children with special educational needs. This study aimed to examine methods for enhancing research skills among students in special education programs at universities in Kazakhstan.MethodsA quasi-experimental research was conducted at two Kazakh universities: Abai Kazakh National Pedagogical University (Almaty) and I. Zhansugurov Zhetysu University (Taldykorgan). The study involved 122 third-and fourth-year students specializing in special education, who were randomly divided into an experimental group (n = 62) and a control group (n = 60). The experimental group participated in an elective course titled “Research Competencies in Special Education” and activities organized by the “Young Scientists Club.” Data collection employed a combination of quantitative and qualitative methods, including pedagogical experiments, surveys, standardized tests, and expert assessments. Statistical analyses were conducted using SPSS software with Student’s t-test to assess differences between groups.ResultsThe experimental group exhibited statistically significant improvements (p < 0.01) compared to the control group in their ability to identify research questions, select appropriate methodologies, analyze data, and apply scientific approaches to practical tasks. Post-intervention assessments indicated that research skills in the experimental group improved markedly (average scores increased from 57.41 to 82.37%). Additionally, students reported higher motivation and confidence in using research methods.DiscussionThe results confirm that integrating targeted educational interventions, combining theoretical coursework and practical research experiences, effectively enhances research competence in future special education teachers. The elective course and participation in the academic club created conditions conducive to active learning and independent research practice. These findings support broader adoption of structured research-based curricula within special education teacher training programs to cultivate critical thinking and evidence-based pedagogical skills.